Clinical and radiographic assessment of composite CAD/CAM endocrowns and stainless steel crowns for endodontically treated first permanent molars in Egyptian children: randomized controlled pilot study - Basheer Ali Mabkhot; Sheriene Ezz Eldin Taha; Shaimaa Mohamed Sabry (BMC Oral Health)
Abstract Background Dental caries in first permanent molars (FPMs) constitutes a worldwide health concern. Managing FPMs with deep dental caries in children poses a significant struggle for dental practitioners. The objective of this research is the clinical and radiographic evaluation of composite CAD/CAM endocrowns as restoration versus stainless steel crowns (SSCs) for endodontically treated FPMs in children. Patients and methods This pilot study evaluated 24 children with deep caries in FPMs attending the dental clinic of Pediatric Dentistry and Dental Public Health Department, Faculty of Dentistry, Cairo University, Egypt. They were randomly assigned to receive either a composite CAD/CAM endocrown (Group I) or an SSC (Group II). Clinical evaluations (postoperative pain, crown retention, patient/parent satisfaction) were performed at one week, three, six, nine, and 12 months. Radiographic assessments (tooth fracture) were done at one week, six months, and 12 months. Results Prior to the intervention, no statistically significant differences were observed between the two groups. No significant differences in postoperative pain scores were observed between groups. Both groups showed good crown retention, with one clinical failure in each group. Patient satisfaction was higher for endocrowns compared to SSCs at three, six, nine, and 12 months. No root fractures were observed in either group. Conclusion Both composite CAD/CAM endocrowns and SSCs showed similar clinical and radiographic outcomes, except for patient satisfaction. Clinicians may consider composite CAD/CAM endocrowns if patient satisfaction is the primary concern. Trial registration Current Controlled Trial NCT05250609. Registered on 22/02/2022, retrospectively registered. https://clinicaltrials.gov/study/NCT05250609 .